Induction of Labor Using Native (OXYTIP) in Comparison to Foreign Oxytocin (SYNTOCINON) - Haghollahi, Fedyeh (Tehran University of Medical Sciences, 2014)
OBJECTIVE: This study was conducted with the aim to investigate and compare Iranian produced and foreign oxytocin for use in induction of labor. MATERIALS AND METHODS: This random clinical trial was conducted on a population of 198 pregnant women with live fetus and cephalic presentation and conditions conducive to induction of labor, monitored by obstetricians and gynecologists. They were randomly divided into group A (n = 99) received 10 units of Syntocinon (Novartis Pharma Canada) in 500 cc Ringer lactate, and group B (n = 99) received 10 units of Oxytip (Caspian Tamin Company Iran) in 500 cc serum, who entered the study to commence induction, by signing written consent. Study variables such as induction indications (post-term, ruptured membranes, diabetes, and..), induction duration, duration of the 1(st) and the 2(nd) stages of labor, and delivery method; as well as labor outcomes like hyper-stimulation of uterine, postpartum bleeding, 5-minute Apgar score, and infant's birth weight; and neonatal outcomes (admission to NICU, oxygen and intubation) were assessed for the two groups by a trained midwife and registered in the patient's questionnaire. Data were analyzed in SPSS software using statistical tests: t-test, Chi-square, and Mann-Whitney. RESULTS: Two groups were similar in demographic variables such as; age, BMI, parity, education. There was no significant difference regarding to obstetric and gynecologic characteristics such as: gestational age, dilatation, effacement, and fetal positioning, as well as the indication for labor induction when the study began. After intervention, variables including: induction duration, duration of the 1(st) and the 2(nd) stages of labor, delivery method; and labor outcomes such as: hyper-stimulation of uterine, postpartum bleeding, 5-minute Apgar score, and infant's birth weight; and neonatal outcomes (admission to NICU, oxygen and intubation), in the two groups, were found to be the same (P < 0.05). Mean oxytip dosage needed was less than that of oxytocin to reach for appropriate pain (P = 0.042). CONCLUSION: The two drugs in terms of labor induction and neonatal complications had similar outcomes and the locally made drug with a lower dosage appears to produce the desired outcome.